151. Molecular diversity and resistance mechanisms of Klebsiella pneumoniae bloodstream infections in Peru. (15th December 2022) - Krapp, Fiorella; Salvatierra, Guillermo; Hinostroza, Noemi; Garcia, Coralith; Astocondor, Aurora L; Ochoa, Theresa; Jacobs, Jan; Garner, Omai; Nizet, Victor; Tsukayama, Pablo
Abstract: Background: Klebsiella pneumoniae, a leading pathogen for mortality associated with antimicrobial resistance (AMR), was responsible for > 250, 000 deaths in 2019. Genomic surveillance can guide the development of vaccines and new antibiotics against this pathogen. While AMR disproportionally affects low-and middle-income countries, limited genomic data are available from these countries. To close this gap, this study provides genomic characterization of K. pneumoniae blood isolates recovered in Peru. Methods: Consecutive non-duplicate K. pneumoniae blood culture isolates were collected during an AMR surveillance study (VIRAPERU) from Jul 2017 to Oct 2019, from 15 tertiary hospitals from 13 regions of Peru. DNA extraction (GeneJET, Thermo Fisher Scientific), DNA library (Nextera XT, Illumina) and genome sequencing (MiSeq 500bp-V2, Illumina) were conducted. De novo assembling (SPAdes v3.13.1), quality assessment and annotation (Nullarbor v2.0), and identification of species, ST group, K/O loci, AMR (Kleborate v2.0.1) were conducted. Phylogenetic trees were built with Microreact v.192. Results: From 119 K. pneumoniae isolates, 114 were recovered and confirmed to belong to the Klebsiella taxon. Six species were identified, the most prevalent being K. pneumoniae (106), followed by K. quasipneumoniae (3). Among carbapenem-resistant isolates (n=13), 10 (77%) carried the bla NDM-1 gene, while other three carried bla KPC-2 (1), bla IMP-16 (1) or no carbapenemase (1). Phenotypic co-resistance to colistin was present in 2 isolates, both negative for mcr-1 gene. The most common mechanisms of resistance to 3 rd generation cephalosporins, quinolones and to aminoglycosides were CTX-M-15 (74.4%), qnrB (63.6%), aac(6')-Ib-cr (87.5%), respectively. Many other AMR genetic determinants were identified (Fig. 1). Sixty ST groups were identified, but only 6 ST groups carried a carbapenemase gene (Fig. 2). A wide diversity of K and O locus was also identified (54 distinct K-loci and 14 distinct O-loci). Figure 1. Genetic determinants of antimicrobial resistance and virulence found in Klebsiella pneumoniae blood isolates of Peru Figure 2. Distribution of ST groups according to specific antimicrobial resistance profiles Conclusion: Bloodstream infections in Peru are caused by a wide diversity of K. pneumoniae strains, carrying multiple AMR genes. Carbapenem resistance is principally a result of bla NDM-1 carriage, found across 6 specific ST groups. Disclosures: Omai Garner, PhD, Beckman Coulter, Inc.: Clinical trial data collection funded by Beckman Coulter, Inc. Victor Nizet, MD, Cellics Therapeutics: Advisor/Consultant|Clarametyx Biosciences: Advisor/Consultant|Vaxcyte, Inc.: Advisor/Consultant|Vaxcyte, Inc.: Grant/Research Support.